The Educational Beliefs of Teachers about Critical Pedagogy - Ayhan Aksakallı (Anı Publishing, 2019)
This study aims to explore the educational beliefs of teachers about critical pedagogy. The participants of the study were chosen through purposive sampling. The study included 55 teachers from different subject areas working in different cities in Turkey. Semi-structured interviews consisting of nine main questions with three explanatory categories were conducted with the teachers. Qualitative data were analyzed through phenomenographic analysis. From the data, two categories regarding educational beliefs were found for the explanatory category "teacher", two categories regarding educational beliefs and two categories depicting descriptions were obtained in the explanatory category "curriculum", as well as the explanatory category "student". This study illustrates the educational beliefs teachers have regarding critical pedagogy within three parameters in the education system (teacher, curriculum, and student). The findings may have a role in addressing prejudices about critical pedagogy and shaping education systems.